2014
DOI: 10.1093/jac/dku001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cefepime dose on mortality of patients with Gram-negative bacterial bloodstream infections: a prospective cohort study

Abstract: High-dose cefepime therapy was associated with lower mortality rates in patients with GNB BSIs, even for GNB with low cefepime MICs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…Using the clinical outcome of those treated with a carbapenem as the comparator, empirical cefepime therapy heralds a similar prognosis and a high-dose cefepime regimen (2 g every 8 h) is independently associated with a better outcome than other dosages, in accordance with a recent prospective observational study (20). Moreover, clinical outcomes were similar among those definitively treated with cefepime and those definitively treated with a carbapenem at the dosages recommended by the CLSI (16).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Using the clinical outcome of those treated with a carbapenem as the comparator, empirical cefepime therapy heralds a similar prognosis and a high-dose cefepime regimen (2 g every 8 h) is independently associated with a better outcome than other dosages, in accordance with a recent prospective observational study (20). Moreover, clinical outcomes were similar among those definitively treated with cefepime and those definitively treated with a carbapenem at the dosages recommended by the CLSI (16).…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, a high-dose regimen of empirical cefepime therapy has been associated with a better prognosis in the cases of bloodstream infections due to a variety of Gram-negative bacilli, and such a therapeutic benefit persists in the isolates with low cefepime MICs (Յ0.25 g/ml) (20). Our data for empirical cefepime therapy for monomicrobial E. cloacae bacteremia support the dose-dependent effect.…”
Section: Figsupporting
confidence: 65%
“…Several clinical studies have associated elevated cefepime MICs with an increased risk of treatment failure and mortality for cefepime-treated patients (1,3,8,9), while other investigations have shown improved clinical outcomes among patients receiving aggressive cefepime dosing for bloodstream infections (BSIs) (10,11). These previous studies lacked PK/PD data, which could be highly useful in interpreting observed outcomes.…”
mentioning
confidence: 99%
“…efepime is a broad-spectrum, fourth-generation cephalosporin commonly used to treat serious infections caused by Gram-negative bacteria (1). For organisms with high MICs, optimal pharmacodynamic targets (time Ͼ MIC) may not be achieved (1,2).…”
mentioning
confidence: 99%
“…For organisms with high MICs, optimal pharmacodynamic targets (time Ͼ MIC) may not be achieved (1,2). Given studies demonstrating cefepime treatment failure of Enterobacteriaceae with elevated MICs, the Clinical Laboratory and Standards Institute (CLSI) adopted a susceptible-dose-dependent (SDD) category in 2014 for cefepime MIC values of 4 and 8 g/ml (3,4).…”
mentioning
confidence: 99%